An Efficient Catalytic Amidation of Esters Promoted by N-Heterocyclic Carbenes - Chen, Ling-Yan; Wu, Mei-Fang (Synthesis, 2019)
An efficient NHC-catalyzed amidation between esters and amines or hydrazines is described. This strategy was tolerant for a wide scope of substrates, affording a series of amides (or hydrazides) in good to excellent yields (60–96%) under simple conditions. The approach was also used to synthesize the pharmaceutically relevant antidepressant moclobemide in 85% yield.
Keywords: N-heterocyclic carbenes; amidation; catalytic reaction; amides; nucleophilic addition